Osobennosti brachnogo povedeniia samtsov Drosophila melanogaster, geterozigotnykh po dominantnoi temperaturochuvstvitel'noi letal'noi mutatsii. [Features of sexual behavior of Drosophila melanogaster males heterozygous for dominant temperature-sensitive lethal mutation.] - Kulikov, A.M.; Mitrofanov, V.G. (Genetika, 1990)
The influence of two mutations on the mate success of Drosophila melanogaster males was studied. Dominant temperature-sensitive lethal mutations l(2)M167DTS and l(2)M65DTS were used in experiments. Both these mutations are recessive lethals in homozygote. Individuals l(2)M65DTS and l(2)M167DTS die at 17 and 28 degrees C, respectively. The mate success of l(2)M65DTS males is much lower than that of normal males. In the experiments conducted in autumn, l(2)M167DTS males were always at advantage, whatever their age. In the winter experiments, they were only at advantage at the age of 2-3 and 15-17 days. For l(2)M167DTS males, a relationship has been established between the mate success and t degrees, and season. The role of behavioural pleiotropic effects of mutations on the probability of their fixation in a population is discussed.